Optimal international division of labour - Herman, Bohuslav; Herman, Bohuslav (fwd.) (Geneva, 1975)
One of the most important ways in which the development of developing countries has been hampered is by obstacles to imports into developed countries of the products in which developing countries are competitive. This is true in particular for industrial products in the production of which relatively little capital and human skill are needed. Even though the low-income countries have been able to increase their exports of these products at an annual rate of 20 per cent, these increases could be much larger if the obstacles were removed. The outcome would be in the long-term interest of both developing and developed countries, but short-sightedness has so far prevented the removal of the obstacles.
Keywords: Labour and labouring classes